2020
DOI: 10.1002/jccs.202000409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Curam drug as an ecofriendly corrosion inhibitor for protection of stainless steel‐304 in hydrochloric acid solution: Chemical, electrochemical, and surface morphology studies

Abstract: In the present work, the Curam drug was used as an eco-friendly corrosion inhibitor for the protection of stainless steel 304 (SS-304) in 2.0 M HCl solution. The inhibition efficiency was determined by mass loss (ML), Potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) measurements. The surface morphology analysis carried out using Fourier transform infrared spectroscopy (FT-IR) and atomic force microscopy (AFM). ML data prove that with an increase in the temperature, Curam sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The results indicated that EAD offered good anti-corrosive properties. The findings of this investigation were in concordance with the outcomes of prior studies of other expired drugs [32][33][34][35].…”
Section: Weight Loss Methodssupporting
confidence: 88%
“…The results indicated that EAD offered good anti-corrosive properties. The findings of this investigation were in concordance with the outcomes of prior studies of other expired drugs [32][33][34][35].…”
Section: Weight Loss Methodssupporting
confidence: 88%
“…Several organic compounds acting as corrosion inhibitors have been evaluated in recent years-for instance, plant extracts [14,[17][18][19][20][21][22][23] and commercial drugs [3][4][5][6][7][8]10,[24][25][26][27][28][29][30]. However, the massive amounts of phytochemicals and drugs that can be tested as corrosion inhibitors need intelligent strategies for their study [31][32][33].…”
Section: Introduction 1corrosion Inhibition and Qsar Fundamentalsmentioning
confidence: 99%